Fungal Ecology in a Tertiary Neonatal Intensive Care Unit after 16 Years of Routine Fluconazole Prophylaxis: No Emergence of Native Fluconazole-Resistant Strains - Luparia, Martina; Landi, Francesca; Mesini, Alessio; Militello, Maria Angela; Galletto, Paolo; Farina, Daniele; Castagnola, Elio; Manzoni, Paolo (American Journal of Perinatology, 2019)
Objective We analyzed the fungal ecology of a neonatal intensive care unit (NICU) over a period of 20 consecutive years following the introduction of routine fluconazole prophylaxis for all very low birth weight (VLBW; <1,500 g at birth) preterm babies. The aim was to detect the possible appearance of any ecological shifts toward the emergence of native fluconazole-resistant (NFR) fungal species.Study Design This was a retrospective analysis of clinical and microbiological data of VLBW preterm neonates admitted to a large tertiary NICU in Italy from 1997 to 2016 and surviving more than 3 days. Colonization and infection incidence rates, both for fluconazole-sensitive Candida spp and NFR Candida spp, were calculated for each year. We compared the first 4-year period without prophylaxis (1997–2000) with the last 16-year period with use of routine fluconazole prophylaxis (2000–2016).Results Overall, the incidence of fungal colonization significantly decreased after the introduction of prophylaxis (from 43.4% to 16.5%) as well as the systemic fungal infection incidence (from 16% to 3.7%). The proportion of colonization and infection by NFR Candida spp, on the other hand, did not increase, remaining stable throughout the 16 years of exposure to fluconazole. During the prophylaxis period, 42 of 1,172 VLBW neonates were colonized by NFR species (3.6%), and of them 11 developed a systemic infection (0.9%). During the preprophylaxis period, colonization by these particular species affected 11 of 285 VLBW neonates (3.8%), and a systemic infection involved 4 neonates (1.4%).Conclusion Fluconazole prophylaxis is effective in decreasing Candida colonization and systemic infections in preterm neonates in NICU and did not cause emergence or shifts toward NFR Candida spp over a 16-year surveillance period.
Keywords: very low birth weight neonate; fluconazole prophylaxis; native fluconazole resistance